2010
DOI: 10.4269/ajtmh.2010.09-0537
|View full text |Cite
|
Sign up to set email alerts
|

A Cholera Outbreak of the Vibrio cholerae O1 El Tor Variant Carrying Classical CtxB in Northeastern Thailand in 2007

Abstract: Cholera outbreaks occurred in Thailand in 2007. Isolates from the northeastern regions were analyzed. Interestingly, the outbreak strain was identified as biotype El Tor; serotype Ogawa with cholera toxin B subunit gene (ctxB) of the classical type and CTX prophage repressor gene of the El Tor type. The clone was genetically closely related to pulsotype H, which is predominantly found in India. It was probably introduced into Thailand recently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
1
9
1
3
Order By: Relevance
“…So far there is no report on the isolation of epidemic strain of V. cholerae O1 with ctxA gene from dogs. These dogs were imported from the north eastern province of Thailand, where cholera was endemic [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far there is no report on the isolation of epidemic strain of V. cholerae O1 with ctxA gene from dogs. These dogs were imported from the north eastern province of Thailand, where cholera was endemic [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A minor difference observed in PFGE profile between isolates in 2010 from the southern provinces may be derived from some mobile elements such as SXT element and integrated filamentous phage genes. Furthermore, currently epidemic El Tor strains in Thailand [19], Laos [22], and Vietnam [23] carry ctx B Cl (El Tor variant). The results of multiplex PCR and PFGE [19,22] suggested that the same epidemic clone is spread widely in Southeast Asian countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, "hybrid strains" that have mixed traits of El Tor and classical biotype were reported in Matlab, Bangladesh. These classical toxin-producing El Tor biotype strains are found globally (Nguyen, Lee, and Cuong, 2009;Okada, Chantaroj, and Roobthaisong, 2010). These classical toxin-producing El Tor biotype strains are found globally (Nguyen, Lee, and Cuong, 2009;Okada, Chantaroj, and Roobthaisong, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This altered El Tor was initially reported in Bangladesh and growing evidence suggests the wide spread of this variant around the world in recent years Okada et al, 2010;Morita et al, 2010;Sithivong et al, 2010;Ceccarelli et al, 2011). The altered El Tor was reported to have fully displaced prototypic seventh pandemic El Tor strains in several countries, including India and Bangladesh Raychoudhuri et al, 2009).…”
mentioning
confidence: 99%